Zmiana miejsca pracy : międzynarodowa analiza zadowolenia zawodowego - Kwiatkowska-Ciotucha, Dorota; Załuska, Urszula (Changing a job : international analysis of job satisfaction, 2005)
The goal of the analysis is the reasons (factors) identification - why an employed person is changing a job. Important issue on job paths analysis is the influence of the perceived level of satisfaction on the job mobility. The other question is: how important for this decision are demographic and social-economic features, such as age, gender, cohabitation status, occupation, industry, firm size. In order to achieve the formulated research goal – the multidimensional statistical analysis framework was used for analysis of the selected information contained in the ECHP database - European Community Household Panel (involving approximately 150,000 respondents from fifteen old EU members).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 162-178